Correlation between Stature and Length of Clavicle in Female Population of Central India (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Anthropology plays an important role in various medicolegal aspects; apart from determinationof Age, Sex and Race of individual, stature is also one of the important parameter of identification variouscivil and criminal cases. Therefore efforts have been made to determine association between stature andlength of clavicle if any.Materials and Method: The present research was carried out in department of Anatomy JNMC Sawangi(M) Wardha; was conducted on total 50 Female individual of age 17–24. The length was calculated withthe help of osteometric callipers for clavicles from anatomical landmarks and stature was calculated incentimetres.Conclusion. From present research it was concluded that the length of clavicle and stature reveals positivecorrelation and the linear relationship between the living stature and length of clavicle of each side wascarried out in the form of regression equation.